2016
DOI: 10.1016/j.pedneo.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fomepizole in Pediatric Methanol Exposure: The First Case Report in Taiwan and a Literature Review

Abstract: Methanol poisoning is rare in the pediatric population, but a delay in diagnosis and intervention may cause severe morbidity and mortality. The current therapy for methanol poisoning is ethanol or fomepizole, which acts as a competitive inhibitor of hepatic alcohol dehydrogenase to inhibit the production of toxic metabolites derived from the oxidation of methanol. However, clinical experience in pediatric methanol poisoning is limited, and the safety profiles of the antidotes have not been established in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The fomepizole-treated patients also showed fewer complications and the best outcome when compared with the non-fomepizole-treated patients. In agreement, a case report study had reported that the use of fomepizole prevented vision defects and stabilized vital signs of a 1 year old who ingested alcohol paste with 80% methanol [37]. In contrast, Holzman, Larsen (2021), reported that all cases of methanol poisoning died despite administering fomepizole and hemodialysis [29].…”
Section: Discussionmentioning
confidence: 76%
“…The fomepizole-treated patients also showed fewer complications and the best outcome when compared with the non-fomepizole-treated patients. In agreement, a case report study had reported that the use of fomepizole prevented vision defects and stabilized vital signs of a 1 year old who ingested alcohol paste with 80% methanol [37]. In contrast, Holzman, Larsen (2021), reported that all cases of methanol poisoning died despite administering fomepizole and hemodialysis [29].…”
Section: Discussionmentioning
confidence: 76%
“…As it has been shown by other authors, inhibition of CYP2E1 by 4-MP significantly decreases oxidative stress [39]. The property of 4-MP to inhibit CYP2E1 and alcohol dehydrogenase is widely used to prevent poisoning with ethanol, methanol and ethylene glycol [39][40][41].…”
Section: Discussionmentioning
confidence: 84%
“…Methanol is metabolized to toxic metabolites by alcohol dehydrogenase. Severe abdominal pain, retina toxicity, acidosis, convulsions, and coma are among its toxic effects (7,26). Exposure to high doses of methanol leads to severe clinical effects such as metabolic acidosis, CNS depression, hypotension, acute renal failure, and methanol blindness (16,26).…”
Section: Methanolmentioning
confidence: 99%
“…Fomepizole does not cause hypoglycemia and sedative side effects, and its tolerability is also more than ethanol. However, its higher cost compared to ethanol restricts its use in clinics (16,(26)(27)(28).…”
Section: Methanolmentioning
confidence: 99%